Therapeutic potential for renal fibrosis by targeting Smad3-dependent noncoding RNAs - Gu, Yue-Yu; Liu, Xu-Sheng; Lan, Hui-Yao (Molecular therapy, 2024)
Renal fibrosis is a characteristic hallmark of chronic kidney disease (CKD) that ultimately results in renal failure, leaving patients with few therapeutic options. TGF-β is a master regulator of renal fibrosis and mediates progressive renal fibrosis via both canonical and noncanonical signaling pathways. In the canonical Smad signaling, Smad3 is a key mediator in tissue fibrosis and mediates renal fibrosis via a number of noncoding RNAs (ncRNAs). In this regard, targeting Smad3-dependent ncRNAs may offer a specific therapy for renal fibrosis. This review highlights the significance and innovation of TGF-β/Smad3-associated ncRNAs as biomarkers and therapeutic targets in renal fibrogenesis. In addition, the underlying mechanisms of these ncRNAs and their future perspectives in the treatment of renal fibrosis are discussed.